Reduced rate of cardiovascular death after cytomegalovirus prophylaxis in renal transplant recipients - Opelz, Gerhard; Döhler, Bernd (Transplantation, 2015)
BackgroundIt is unknown how death with a functioning graft (DWFG) is affected in renal transplant recipients who receive prophylaxis for cytomegalovirus (CMV) infection.MethodsData from 61,927 adult recipients of a deceased donor kidney transplant in 1990 to 2012 registered with the Collaborative Tr